Use of multiple social media platforms and symptoms of depression and anxiety: A nationally-representative study among U.S. young adults. (April 2017) - Primack, Brian A.; Shensa, Ariel; Escobar-Viera, César G.; Barrett, Erica L.; Sidani, Jaime E.; Colditz, Jason B.; James, A. Everette
Abstract: Introduction: While increased time spent on social media (TSSM) has been associated with depression and anxiety, the independent role of using multiple social media (SM) platforms is unclear. Methods: We surveyed a nationally-representative sample of 1787 U.S. young adults ages 19–32. Depression and anxiety symptoms were measured using the Patient-Reported Outcomes Measurement Information System (PROMIS). We assessed use of multiple SM platforms with an adapted Pew Internet Research scale. We used ordered logistic regression models to assess associations between use of multiple SM platforms and mental health outcomes while controlling for eight covariates, including overall TSSM. Results: Compared to those who used 0–2 social media platforms, participants who used 7–11 social media platforms had substantially higher odds of having increased levels of both depression (Adjusted Odds Ratio [AOR] = 3.0, 95% CI = 1.9–4.8) and anxiety symptoms (AOR = 3.2, 95% CI = 2.0–5.1). Associations were linear (p < 0.001 for all) and robust to all sensitivity analyses. Conclusions: Use of multiple SM platforms is independently associated with symptoms of depression and anxiety, even when controlling for overall TSSM. These associations are strong enough that it may be valuable for clinicians to ask individuals with depression and anxiety about multiple platform use and to counsel regarding this potential contributing factor. Highlights: We found a linear association between the number of platforms used and depression. We found a linear association between the number of platforms used and anxiety. Associations remained strong after controlling for total time of social media use.